KINERJA GURU SEJARAH SMA DI KOTA METRO - Kuswono Kuswono (HISTORIA : Jurnal Program Studi Pendidikan Sejarah, 2015)
The aim of this study was to describe the performance of high school history teacher in Metro City. Assess teacher performance in the history of the city's Metro As infromasi for measures of performance development in the history teachers to meet curriculum of 2013. This type of research is quantitative descriptive using the survey method. This study will assess the performance of teachers and the entire population of high school history teacher in Metro City. The sampling technique using disproportionate stratified random sampling, data collection techniques using a questionnaire using Likert scale. The maximum score 7 so that teacher performance can be compared with scores obtained from each school that SMA 1 Metro get the value of 6.59. SMAN 2 Metro get a score of 6, 17. SMAN 3 Metro has a score of 4.03. SMAN 4 get a score of 5.33. SMAN 5 get a score of 6.61 and SMAN 6 get a score of 5.91. Performance history teacher high schools in Metro City is at a good level.